Early transmission dynamics of SARS-CoV-2 in Indonesia - Mudatsir Mudatsir; Synat Keam; Wira Winardi; Amanda Yufika; Ali A. Rabaan; Alfonso J. Rodriguez-Morales; Kuldeep Dhama; Abram L. Wagner; Harapan Harapan (Trends in Infection and Global Health, 2021)
The objective of this study was to determine the transmission dynamics of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and to evaluate the vigilance of the health system during the early phase of coronavirus disease 2019 (COVID-19) outbreak in Indonesia. The early epidemiology and transmission chains of COVID-19 were analyzed based on data from the Directorate General of Disease Prevention and Control of the Indonesian Ministry of Health. The results of this study shown although Indonesia is a country with a high relative importation risk of SARS-CoV-2, the first two cases of COVID-19 were identified on March 2, 2020. This relatively late date by regional standards raises the possibility of undetected cases beforehand. The first case was a foreigner citizen who visited the capital city of Jakarta and later was diagnosed COVID-19 after returning from Indonesia. One week later after the first case, 27 confirmed COVID-19 cases had been reported in Indonesia, and the majority of the cases were clustered together. Apart from the possibility of underdetection of COVID-19 cases in the country, the government has strengthened the disease surveillance system and established an outbreak preparedness system to diagnose and control COVID-19.